Investigation the effects of reservoir operation on providing different demands by System Dynamics (Case study: Kowsar dam in Iran) - ,F. raeiszadeh ,S. Farzin, M.H.Ahmad, R. rajabpour (International Journal of Scientific Research and Management (IJSRM), 2014)
:Nowadays, beside water shortage, we face with mismanagement in water resources. In this situation, optimal water management especially in arid and semi-arid areas is very important. Increasing water demands due to population growth, industrial and agricultural developments are inevitable. On the other hand, water resource limitations and principal of sustainability in water management, cause water allocation, very challenging work. So for answering to agricultural, municipal, industrial and ecological demands with high reliability, we need very exact programs. The purpose of this paper is to investigate the effect of storage dam on Kheirabad River in Tange-Dook area for floodwater collection at raining times and also providing so called demands. For modeling, we used VENSIM because of existence of dynamic relations between so called factors. Based on findings of this study, it was shown that beside simplicity and good accuracy, this model has a very good adaptability with various conditions of dam’s water allocations.